ALGUMAS OBSERVAÇÕES ACÊRCA DE Antarctia fusca (WALKER, 1812) (LEP, ARCTIIDAE) - Lordello, Luiz Gonzaga E.; Rodrigues, Rubens Alves (REVISTA DE AGRICULTURA, 2016)
ALGUMAS OBSERVAÇÕES ACÊRCA DE Antarctia fusca (WALKER, 1812) (LEP, ARCTIIDAE)